Portrayal of traditional psychotherapeutic context in j. p. clark's song of a goat (2022)
Traditional medicine, in its rea context, is the totality o f the ancient manner and means o f restoring, preserving and protecting health. The objective is to sustain practices t at promote the wellbeing o f the people particularly, before the advent o f modem medicine . The approaches to the sustenance o f health as a social welfare paclcage for peoples are adapted from and to traditiona, religious beliefs and values o f each community, which are generationally transferred. Traditional medicine offers diverse areas o f specialisation which include herbal medicine, midwifery, and treatment o f infertility, mental healing and somatic therapy. This paper therefore unjacks the traditional psychotherapeutic context portrayed in J.P Clark's Song o f a Goat. Through descriptive qualitative research design and instrumentalities o f combination o f both traditional psychotherapy and behaviour therapy, the paper underscores the roles a traditional psychother pist plays among the Urhobo and Izon peoples ofN iger Delta, on family matters and the responses o f the clients portrayed under psycho-social a id cultural contexts. These foreground existing psychotherapeutic forms, peculiarly the systemic which comprises of: counselling psychology, marriage and family therapy and body psychotherapy: exercise, massage and sexuality. The symptoms portrayed in the cases examined in this study, chiefly on family therapeutic discourse, further reinforce the reality o f the diagnosis of disorders; defences and outrage ii particular and it’s rippling effect